Healthcare Workers' Strategies for Doffing Personal Protective Equipment. (13th September 2019) - Baloh, Jure; Reisinger, Heather Schacht; Dukes, Kimberly; da Silva, Jaqueline Pereira; Salehi, Hugh P; Ward, Melissa; Chasco, Emily E; Pennathur, Priyadarshini R; Herwaldt, Loreen
Abstract: Background: Personal protective equipment (PPE) helps protect healthcare workers (HCWs) from pathogens and prevents cross-contamination. PPE effectiveness is often undermined by inappropriate doffing methods. Our knowledge of how HCWs approach doffing PPE in practice is limited. In this qualitative study, we examine HCWs' perspectives about doffing PPE. Methods: Thirty participants at a Midwestern academic hospital were recruited and assigned to 1 of 3 doffing simulation scenarios: 3 mask designs (n = 10), 2 gown designs (n = 10), or 2 glove designs (n = 10). Participants were instructed to doff PPE as they would in routine practice. Their performances were video-recorded and reviewed with participants. Semistructured interviews about their doffing approaches were conducted and audio-recorded, then transcribed and thematically analyzed. Results: Three overarching themes were identified in interviews: doffing strategies, cognitive processes, and barriers and facilitators. Doffing strategies included doffing safely (minimizing self-contamination) and doffing expediently (eg, ripping PPE off). Cognitive processes during doffing largely pertained to tracking contaminated PPE surfaces, examining PPE design cues (eg, straps), or improvising based on prior experience from training or similar PPE designs. Doffing barriers and facilitators typically related to PPE design, such as PPE fit (or lack of it) and fastener type. Some participants also described personal barriers (eg, glasses, long hair); however, some PPE designs helped mitigate these barriers. Conclusions: Efforts to improve HCWs' doffing performance need to address HCWs' preferences for both safety and expediency when using PPE, which has implications for PPE design, training approaches, and hospital policies and procedures. Abstract : Healthcare workers seek both safety and expediency when doffing personal protective equipment (PPE). While doffing, they track contaminated surfaces, follow design cues, and rely on experience to improvise. They encounter numerous doffing barriers and facilitators, chiefly pertaining to PPE design.